Fluoroquinolone resistant Escherichia coli in community: molecular analyses of resistance genes, virulence factors, and antimicrobial susceptibility test - Tano, Zuleica Naomi; Soncini, João Gabriel; Koga, Vanessa Lumi; Pimenta, Julia Silva; Castilho, Pedro Olimpio Siqueira; Moreira, Maria Julia Onça; Cardoso, Alanis Cassamassimo; Sugiura, Larissa; Kobayashi, Renata Katsuko Takayama; Lincopan, Nilton; Pavanelli, Wander Rogério; Vespero, Eliana Carolina (Frontiers in Microbiology, 2026)
IntroductionMost urinary tract infections in all populations are caused by gram -negative, facultative anaerobic, uropathogenic E. coli (UPEC). Multidrug resistance (MDR) to first line antibiotics recommended for treatment of UTI is a global health problem. The misuse of antimicrobial agents for UTI treatment can lead to selection of bacterial MDR, able to transfer mechanism of resistance through mobile genetic elements (MGEs), such as transposons, integrons and conjugative plasmids. This study aims to characterize MLST, virulence and resistance genes to quinolones and β-lactams of UPEC samples isolated from UTI in community.MethodsE. coli strains were isolated from urine samples from June 2016 to June 2018. The identification and bacterial susceptibility were realized by automated VITEKⓇ2 system. Enterobacterial Repetitive Intergenic Consensus (ERIC-PCR) was performed to assess genetic similarity. The DNA was used to construct a paired-end library, which was sequenced using the NextSeq platform (Illumina). Genome assemblies was performed by the CLC Genomics Workblench version 7.0. Multilocus sequence type (MLST), resistome and virulome were identified using bioinformatics tools available from the Center for Genomic Epidemiology.ResultsThis study analyzed 54 E. coli isolates resistant to fluoroquinolones and/or producing ESBLs. High resistance rates were observed for ampicillin (100%), nalidixic acid (96.6%), ceftriaxone (83.3%), cefepime (81.5%), ciprofloxacin (81.5%), norfloxacin (81.5%), sulfamethoxazole/trimethoprim (75.9%), and nitrofurantoin (71.9%). Genomic analysis revealed 25 sequence types (STs), with ST131 being most prevalent (22.2%), and 29 serotypes, notably O25:H4 (16.7%). Furthermore, it also showed β-lactam resistance genes including blaCTX-M (77.8%), mainly blaCTX-M-15 (25.9%), and others like blaTEM-1B and blaOXA-1. Mutations in gyrA (S83L, D87N) and parC (S80I) were common (98.1%), along with plasmid-mediated resistance (PMQR), such as aac(6’)-Ib-cr (13%). Virulence genes commonly linked to UTIs were detected, with iss (72.2%) being the most frequent. Most isolates had up to three virulence genes. Plasmids were detected in nearly all isolates, especially IncF.DiscussionThis study reveals the widespread circulation of high-risk, multidrug-resistant UPEC clones in community-acquired UTIs, particularly those belonging to the globally disseminated ST131 lineage. The frequent coexistence of resistance determinants, virulence factors, and IncF plasmids highlights the adaptive success of these strains and their potential for sustained dissemination. These findings emphasize the need for continuous genomic surveillance, rational antimicrobial use, and region-specific treatment guidelines to mitigate the impact of MDR UPEC in the community.